Cities and Local Governments in Central Asia - Junussova, Madina (Taylor & Francis, 2025)
This book presents the changing roles of urban governments and how local governments struggle to gain administrative, fiscal, and political power to combat current urban challenges in Kazakhstan. Focusing on the cities and regions selected by the national government of Kazakhstan to be the drivers of national economic development, the author analyses the impact of decentralization on the role of local governments. The book examines the practical experiences of city and regional governments with an emphasis on urban planning, public investment in national projects, and management of urban transport. Due to the complexity and irregular distribution of political reforms at different levels of local government in Kazakhstan, three separate studies are presented, each looking at a specific aspect of decentralization reform and local government function related to physical urban development and distribution of public investment. The author argues that, if the national government of Kazakhstan wants to concentrate economic resources in urban agglomerations, it is not enough to assume that local governments are ready to play the role of efficient planners and managers of urban development. A useful analysis illustrating cities and urban conglomerations as engines of growth in economic development, this book will be of interest to academics studying Central Asian Studies, in particular political and economic development, Development Studies, and Urban Studies. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license